Honesty and Empathy Character-building Training for Children Under Care of Foster Parents - Nurlaili Wangi, Eneng; Rosiana Dewi Sartika, Dewi; Aslamawati, Yuli; Mutya Lutfiani, Siti (KnE Social Sciences, 2023)
SOS Childrens Villages is a non-profit, non-governmental social organization that actively supports childrens rights, namely a loving family and home. In this case, SOS Childrens Villages is committed to providing shelter and care for children who have or are at risk of losing their parental care. To increase the ability of foster parents, it is necessary to provide further training on improving parenting skills about honesty and empathy to foster parents through roleplay and case examples. A focused group discussion was conducted to collect the data from 12 foster parents. The results of this training were effective where foster parents have succeeded in increasing their knowledge and skills in applying the values of honesty and empathy. The suggestion in this study is that it can be held offline so it will be easier for parents to understand the material. For the next collaboration, the training will be discussed in more depth what underlies the honesty or openness of children and empathy for children. Keywords: honesty, empathy, children, SOS children village